Consumer Driven Energy Drink Development - Workshop - Isaev, Samet; Makatsoris, Harris (Cranfield University, 2018)
This project explores a novel methodology for design and manufacture of consumer-driven personalised Energy Drinks (ED) using novel technologies developed by the research group. Initially, a novel online crowdsourcing OI platform named ‘Preference Marketplace’ is used to identify consumer’s preferences & sensory attributes for the formulation of ED and then followed by manufacturing of consumer-preferred ED using a novel automated continuous flow manufacturing reactor for sensory evaluation. By combining the two technologies, it is now possible to produce an economical and sustainable on-demand formulated liquid food products that meet consumer needs.
Keywords: 'Open Innovation'; 'Web-based creation'; 'Preference Marketplace'; 'Consumer-driven new product development'; 'Manufacturing Processes and Technologies (excl. Textiles)'; 'Manufacturing Management'; 'Process Control and Simulation'